PENENTUAN UMUR PANEN BEBERAPA GENOTIPE PADI (Oryza sativa L.) BERDASARKAN SATUAN PANAS PADA SISTEM BUDIDAYA ORGANIK DAN NON ORGANIK - Putri, Della Alvia Kusuma; Dulbari, Dulbari; Sudrajat, Denny; Subarjo, Subarjo; Jaya, Moh. Haris Imron S. (Universitas Lampung, 2025)
Determining the harvest time of rice plants is one of the determining factors for the success of rice production. Calculation of harvest time can be done using the heat unit method. This study aims to calculate the accumulation of heat units of several rice genotypes (Oryza sativa L.) in organic and non-organic cultivation systems. This study was conducted in September-December 2023 at Polinela Organic Farm (POF), Lampung State Polytechnic (5°21'10